Learning and Work Design - Jairo Eduardo Borges-Andrade; Nara Saddi de Paiva Sampaio (Revista Psicologia)
Complex work environments require continuous development, promoted by professionals themselves, when those environments are favorable. The relationships between work design, learning strategies used by individuals, and professional development are the focus of this article. Data collection took place in three moments over six months. It involved 91 participants in three privately owned organizations. Current professional development was first measured. In the second moment, data on dimensions of work design was collected. In the third moment, learning strategies and evolutionary and current professional development were measured. Pearson correlations suggest that the use of practical application and active reflection, two types of learning strategies, seems to be associated with prior characteristics of work design that include autonomies of decision and use of methods, in varied tasks that require problem solving using diversified skills, but that provide feedback. Practical and research implications are discussed.